2009
DOI: 10.1111/j.1469-8137.2009.02879.x
|View full text |Cite
|
Sign up to set email alerts
|

To duck or not to duck: resistance advantages and disadvantages of the candy‐cane stem phenotype in tall goldenrod, Solidago altissima

Abstract: Summary• Solidago altissima populations consistently contain a minority of 'ducking', or 'candy-cane', stems. The goals of this study were to investigate whether these candy-cane stems may be an adaptation to resist herbivory, and to look for costs (namely, resistance tradeoffs or reduced reproduction) that might constrain the spread of the ducking trait.• In this study, herbivory and seed set were recorded for 272 erect and 272 candycane stems in a field population of S. altissima.• Candy-cane plants were twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 32 publications
1
34
2
Order By: Relevance
“…Goldenrod resistance and tolerance -Many studies have demonstrated signifi cant genetic variability in goldenrod resistance to insect -herbivore attack ( Maddox and Root, 1987 ;McCrea and Abrahamson, 1987 ;Maddox and Root, 1990;Cronin and Abrahamson, 2001b ;Wise, 2009 ), but few have examined costs and/or selection for resistance ( Uriarte et al, 2002 ;. These few studies suggest that there is generally strong selection for increased resistance, but there is low broad-sense heritability for resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Goldenrod resistance and tolerance -Many studies have demonstrated signifi cant genetic variability in goldenrod resistance to insect -herbivore attack ( Maddox and Root, 1987 ;McCrea and Abrahamson, 1987 ;Maddox and Root, 1990;Cronin and Abrahamson, 2001b ;Wise, 2009 ), but few have examined costs and/or selection for resistance ( Uriarte et al, 2002 ;. These few studies suggest that there is generally strong selection for increased resistance, but there is low broad-sense heritability for resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Candy-cane genets initially grow erect stems, but their apices begin to nod after approximately 4 weeks until they point downward to look like candy-canes. Candy-cane genets are resistant to tephritid and cecidomyiid gallers that induce galls in apical meristems (Wise and Abrahamson 2008;Wise 2009). When the stems of candy-cane genets are straightened through exposure to strong shade, their resistance to herbivores disappears, suggesting that the nodding architecture of the candy-canes is responsible for the resistance (Wise et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel plant architectural trait was demonstrated to provide resistance to insect herbivory (Wise and Abrahamson 2008;Wise 2009;Wise et al 2009Wise et al , 2010a. In the tall goldenrod Solidago altissima in the United States, most genets have erect stems, while some genets have stems with nodding apices ('candy-cane' genets).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations